Latihan Fisik dan Obesitas pada Remaja - Andi Pranata; Widyatuti Widyatuti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the relationship between physical exercise and obesity in adolescents. The method used is a systematic review using four databases: ClinicalKey Nursing, Emerald Insight, Sage Journals, and ScienceDirect. The results showed that of the thirteen articles reviewed, nine pieces showed that regular physical exercise could reduce body weight, body mass index (BMI), body fat percentage, and body composition. Physical exercise is also related to obesity status and is a strategy to control obesity as well as an obesity prevention factor which is not only recommended to prevent obesity but can maintain a healthy body; lack of physical exercise can increase the risk of obesity by 3.08 times greater than adolescents who do exercise physique. Four other articles stated that obesity in adolescents was not directly related to physical exercise. Still, they reported the occurrence of obesity due to food consumption habits that can increase body fat. In conclusion, physical exercise is recommended as a strategy for preventing and managing obesity. It is associated with obesity status in adolescents, which can be known from the value of body mass index (BMI). Keywords: Physical Exercise, Obesity, Adolescents